Socio economic predictors of HIV infection among 14-35 years old in rural South Africa - Fadahun, Oluwafolajimi Olusesi (My University, 2010)
Focus in public health research is shifting to the role of socio-economic factors in the promotion of health. Hence, an understanding of the roles socio-economic factors plays in improving health and health-seeking behaviour is important for public health policy. This study examined the relationship between socio-economic factors and HIV infection in rural Limpopo Province South Africa, an area characterized by poverty differentials and migration. Various possible social and economic risk factors (such as nationality, education status, marital status, employment status, migration status and socio-economic status) for HIV infection are analysed and discussed. This is secondary data analysis was carried out during the period June 2001 to March 2005 among 2345 14-35 year old residents in eight (8) villages in rural Limpopo. Married participants (OR 0.53 [95%CI 0.28 – 1.00]), those from poor (OR 0.49 [95%CI 0.28-0.85]) and less poor households (0.38 [95%CI 0.21-0.70]) are less likely to contract HIV infection. Noteworthy from these analyses also is the increased risk for HIV infection seen among female participants, those not currently schooling (OR 1.9 [95%CI 1.2 – 3.3]) and non-South African citizens (OR 5.18 [95%CI 1.04-25.8]). Conclusion: Women, out-of school youths and non South African citizens are shown to be high-risk population groups for HIV infection. HIV prevention programs that target identified vulnerable population groups and increased social support for the family may contribute to mitigating the spread of HIV in rural South Africa.
MSc (Med) Epidemiology and Biostatistics, Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: risk factors; HIV infection; socio-economic conditions